2017
DOI: 10.1590/1413-70542017415013417
|View full text |Cite
|
Sign up to set email alerts
|

Green manuring with Calotropis procera for the production of coriander in two growing seasons

Abstract: The use of spontaneous species of the Caatinga biome can contribute significantly to the nutritional demand of vegetable crops, thereby providing an agroecological and sustainable form of production. The objective of this research was to determine the effects of different biomasses of Calotropis procera (rooster tree) and times of incorporation into the soil of green manure during two growing seasons on the agronomic performance of coriander cv. Verdão produced in Serra Talhada, a semi-arid region of Pernambuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Reducing-cost-technology (RCT) consisted of the soil nontillage and decreasing nitrogen over-fertilizing doses with green manures before crop patterns. Those plants have high potential for restoration of soil fertility and enhancement of terrestrial crop production [34] and provided best profits compared with the other plants (Whitmore A. P. et al, 2000) [35], also contributed significantly to the nutritional demand of green manure legumes, thereby providing an agro-ecological and sustainable production [36]. The grazing of green manure, especially oat (Avena sativa), pea/oat (A. Sativa/Pisum sativum) contributed to improving the available nitrogen production in integrated crop-livestock systems [37].…”
Section: Quality and Quantity Of Yield Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing-cost-technology (RCT) consisted of the soil nontillage and decreasing nitrogen over-fertilizing doses with green manures before crop patterns. Those plants have high potential for restoration of soil fertility and enhancement of terrestrial crop production [34] and provided best profits compared with the other plants (Whitmore A. P. et al, 2000) [35], also contributed significantly to the nutritional demand of green manure legumes, thereby providing an agro-ecological and sustainable production [36]. The grazing of green manure, especially oat (Avena sativa), pea/oat (A. Sativa/Pisum sativum) contributed to improving the available nitrogen production in integrated crop-livestock systems [37].…”
Section: Quality and Quantity Of Yield Improvementmentioning
confidence: 99%
“…Pieters A, J., 1927). In the study conducted by Zandvakili showed that the roots had higher concentrations of nourishments than shoots [36,48]. found that the use of native species of the Caatinga Biome could affect the nutritional demand of the Market of Garden Crops significantly, thus providing a form of agro-ecological and sustainable production.…”
Section: Improvement Of Soil and Biodiversity's Healthmentioning
confidence: 99%